Biodegradable cellulose-based aerogel from recycled paper / Sarifah Fauziah Syed Draman ... [et al.] - Syed Draman, Sarifah Fauziah; Mohd, Norzila; Salleh, Mohd Shahrul Nizam; Ahmad, Nurul ‘Uyun (2018)
The increasing amount of recycled paper generated around the world has caused disposal problems to the environment. Valuable material such as cellulose can be extracted from these recycled papers. Then, cellulose-based hydrogel and cellulose- based aerogel will be prepared since most of the available hydrogel and aerogel are made from non-renewable and non-biodegradable materials. Hydrogel is a material exhibit the three-dimensional hydrophilic polymer structure that can absorb and hold great amount of water, saline or physiological solutions and have been generally utilized as part of agricultural, biomedical field, tissue building. Aerogel is a highly porous solid material, exhibit a several of unique characteristics including ultralow density, high specific surface area as well as high porosity. In this study, cellulose from recycled paper was extracted using deep eutectic solvent (DES), which composed choline chloride and urea. Then, hydrogels was prepared from extracted cellulose in NaOH/Urea solvent by using epichlorohydrin (ECH) as a cross-linker. The cellulose-based aerogels from recycled paper also was prepared using NaOH/Urea solvent. Characterization and chemical analysis of extracted and produced materials were carried out with Fourier Transform Infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Furthermore, optimum condition to produce cellulose-based hydrogel and aerogel not widely been discussed yet. To perform the optimization process, software named Design-expert was utilized in order to use the technique of response surface methodology (RSM). Central composite design (CCD), which is one of the methods in RSM was used to analyzed the response in order to optimize the hydrogel and aerogel. Based on the results of this experiment, it is expected optimum condition can be achieved.